Ultrasonography for Verification of Endotracheal Tube Position in Neonates and Infants - Sheth, Mansi; Jaeel, Pooja; Nguyen, Jimmy (American Journal of Perinatology, 2017)
Objective Ultrasonography (US) has been shown to be effective for verifying endotracheal tube (ETT) position in adults and older children but has been less studied in the neonates and infants. The literature regarding US utility for ETT positioning in this population is reviewed.Study Design A literature search was conducted using the EMBASE, Google Scholar, MEDLINE, Ovid, and Scopus databases with search terms regarding US relating to ETT intubation and positioning in neonates and infants.Result Nine relevant studies were included for review. All studies report > 80% visualization of the ETT tip by US. US interpretation of the ETT position correlated with the radiography position in 73 to 100% of cases when the ETT tip was visible. There were variations in technique, sonographer, and sonographer training between studies.Conclusion US appears to be well tolerated by neonates and infants and may augment the determination of proper ETT position. Further studies are needed regarding optimal technique and sonographer training.
Keywords: endotracheal tube; ultrasound; ultrasonography; point-of-care US; intubation; neonate; infant